2016
DOI: 10.1088/1674-1056/25/6/060507
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of an air conditioning system with entropy generation minimization and entransy theory

Abstract: In this paper, based on the generalized heat transfer law, an air conditioning system is analyzed with the entropy generation minimization and the entransy theory. Taking the coefficient of performance (denoted as COP) and heat flow rate Q out which is released into the room as the optimization objectives, we discuss the applicabilities of the entropy generation minimization and entransy theory to the optimizations. Five numerical cases are presented. Combining the numerical results and theoretical analyses, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
(103 reference statements)
0
2
0
1
Order By: Relevance
“…It is also very clear that the entransy dissipation minimization gives the minimum value of Eq. (43). When the optimization objectives in these systems are obtained, we have shown that the heat transfer temperature differences are uniform.…”
Section: Consistence Between the Uniformity Principle Of Temperature ...mentioning
confidence: 92%
“…It is also very clear that the entransy dissipation minimization gives the minimum value of Eq. (43). When the optimization objectives in these systems are obtained, we have shown that the heat transfer temperature differences are uniform.…”
Section: Consistence Between the Uniformity Principle Of Temperature ...mentioning
confidence: 92%
“…For the two objectives, research showed that the applicability of the EGM is also conditional. [21,38] The effects from different heat transfer laws were analyzed, [38] and the conclusions still hold.…”
Section: Analyses Of Other Objectivesmentioning
confidence: 99%
“…该原理表明, 在满足一定条件时, 系统的最大 损失 对 应 于 系 统 的 最 大 输 出 功 . 该 原 理 已 在 卡 诺 循 环 [29,44,49,51,56] 、热泵系统 [23,52] 以及奥拓循环 [53,54] 等多 种热力学系统中获得应用. 但与此同时, 也存在对 理 论科学性和应用价值的质疑, 认为 理论与熵理论在 热力学分析中并无区别 [57] .…”
Section: 由于 的概念和相关原理从新的角度阐释和揭示了热 物理过程的客观规律 该理论已应用到多种不同的传 热和热功转换系统的分析unclassified